Small angle X-ray scattering analysis of Cu2+-induced oligomers of the Alzheimer's amyloid β peptide. Issue 3 (11th March 2015) - Ryan, Timothy M.; Kirby, Nigel; Mertens, Haydyn D. T.; Roberts, Blaine; Barnham, Kevin J.; Cappai, Roberto; Pham, Chi Le Lan; Masters, Colin L.; Curtain, Cyril C.
<x xml:space="preserve">Abstract</x> Research into causes of Alzheimer's disease and its treatment has produced a tantalising array of hypotheses about the role of transition metal dyshomeostasis, many of them on the interaction of these metals with the neurotoxic amyloid-β peptide (Aβ).